2014
DOI: 10.1074/mcp.m113.033464
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protein Interactions with Endoglin and Activin Receptor-like Kinase 1: Potential Role in Vascular Networks

Abstract: Endoglin and activin receptor-like kinase 1 are specialized transforming growth factor-beta (TGF-␤) superfamily receptors, primarily expressed in endothelial cells. Mutations in the corresponding ENG or ACVRL1 genes lead to hereditary hemorrhagic telangiectasia (HHT1 and HHT2 respectively). To discover proteins interacting with endoglin, ACVRL1 and TGF-␤ receptor type 2 and involved in TGF-␤ signaling, we applied LUMIER, a high-throughput mammalian interactome mapping technology. Using stringent criteria, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 47 publications
0
24
0
1
Order By: Relevance
“…Our recent study (11) demonstrated protein interactions between many Rho GTPases and TGF‐β receptors. Pak‐1 interacted with ENG, TGFBR2, ALK1, and ALK5 (11, 16), whereas Rac‐2 and Rab38 interacted with the first 3. RhoH interacted with ALK1, RhoJ and Rasl with ALK1 and TGFBR2, and Arl8B with ENG and TGFBR2 (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our recent study (11) demonstrated protein interactions between many Rho GTPases and TGF‐β receptors. Pak‐1 interacted with ENG, TGFBR2, ALK1, and ALK5 (11, 16), whereas Rac‐2 and Rab38 interacted with the first 3. RhoH interacted with ALK1, RhoJ and Rasl with ALK1 and TGFBR2, and Arl8B with ENG and TGFBR2 (11).…”
Section: Discussionmentioning
confidence: 99%
“…Human embryonic kidney‐293T cells were seeded in 6‐well plates at 2.5 × 10 5 cells perwell and transfected with 1 μg total plasmid DNA (RhoA‐Flag, with or without ENG) using FuGENE 6 (Hoffmann‐La Roche Limited, Mississauga, ON, Canada). The preparation of cell lysates, immunoprecipitation (IP), and Western blot (WB) were carried out as described (11). The P4A4 mAb to ENG (1 μg) was used for IP and the mouse anti‐Flag (M2) antibody (Sigma‐Aldrich, Oakville, ON, Canada) for WB.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…High‐throughput interactome mapping recently identified 181 novel interactors between ACVRL1, the TGF‐β receptor‐2, and endoglin, including protein phosphatase subunit β (PPP2RB). In turn, PPP2RB was shown to disrupt endothelial nitric oxide synthase signaling in endoglin‐deficient cells in vitro , identifying a potential role for PPP2RB in the pathobiology of HHT …”
Section: Applied Systems Biology: Influences In Clinical Medicinementioning
confidence: 99%